The Relationship between Inferiority Complex and Educational Methods among Students in the Kindergarten Department at the University of Sulaimani - Abdulsamad Ahmad Mohammed (Zanco Journal of Human Sciences, 2025)
This study aimed to determine the relationship between inferiority complex and educational methods among kindergarten students at the University of Sulaimani. To achieve this goal, the researcher used the (analytical description) method appropriate to the content of the study. The research community consists of 220 female students from kindergarten. The study sample includes first and third year students, first year (62) students, and third year (47) students. The research tool is a survey form consisting of 44 paragraphs, 22 paragraphs of which relate to the first variable (inferiority complex) and 22 paragraphs relate to the second variable (educational methods). The statistical tools include computational means to extract validity, and two-sample tests to determine the difference between two variables. Finally, it was found that there is an inferiority complex among kindergarten students, which means that the development of this mental problem is directly related to educational methods.